SYNONYMY MEANING RELATIONSHIP IN THE SOCIETY’S DAILY CONVERSATION AT UNDISAN VILLAGE, TEMBUKU DISTRICT, BANGLI REGENCY - I G. AG.I. ARYANI,; I NYM. TRI EDIWAN,; N. K. S. RAHAYUNI,; PT. EVI WAHYU CITRAWATI, (SPHOTA: Jurnal Linguistik dan Sastra, 2016)
ABSTRACT This research aims to analyze the relationship of synonym meaning found in Bali language at Undisan, Tembuku district, Bangli Regency. Qualitative analysis was used to explain the result of findings from six respondents who lived in this village. Generally, language variation of synonym developed because of the contact between languages (Bali, Indonesia and English) in the society and their occupation. The synonymy of word or phrase in a sentence found in Bali language were compared with the use other part of Bali for their similarity of meaning or difference depend on their use by referring to the dictionary of Bali-Indonesia-English and information from the society. The purpose is to identify the similarities or differences of meaning found in the daily conversation synonymy of intra-lexical items, formal or informal languages used by adults or children. The study was descriptively analyzed by using qualitative approach based on datas finding in the location using observation method from the respondents to search detail of information required. Relation of meaning analyzed based on the finding through observation and contact involvement method with the respondents. Key words: lexical, meaning relationship, and synonym